The Relationship between Work Motivation and Employee Performance at the Education and Culture Office of South Tangerang City - Sakinah, Elvi; Anisah, Anisah; Setiawati, Merika; Febrianti, Sari (Journal of Educational Management Research, 2025)
This research is motivated by the phenomenon that shows there are still employees whose performance and work motivation are not optimal in carrying out their duties and responsibilities. The purpose of this study is to obtain data and information about employee performance, employee work motivation, and whether there is a relationship between work motivation and employee performance in carrying out duties at the Education and Culture Office of South Tangerang City. This study uses a quantitative method with a correlational approach and proportional random sampling technique with a total of 112 employees as respondents. The research instrument is a questionnaire with a Likert scale that has been tested for validity and reliability. The results show that employee work motivation is in the very good category (90%), and employee performance is also in the very good category (91%). There is a significant relationship between work motivation and employee performance, with r count 0.549 > r table 0.184 and t count 6.880 > t table 1.658 at a significance level of 95%. In conclusion, work motivation has a significant effect on employee performance at the Education and Culture Office of South Tangerang City.